Choice of Cell Source in Cell-Based Therapies for Retinal Damage due to Age-Related Macular Degeneration: A Review - Sudhakar John; Sundaram Natarajan; Periyasamy Parikumar; Mahesh Shanmugam P; Rajappa Senthilkumar; David William Green; Samuel J. K. Abraham (Journal of Ophthalmology)
Background. Age-related macular degeneration (AMD) is a complex disorder that affects primarily the macula involving the retinal pigment epithelium (RPE) but also to a certain extent the photoreceptor layer and the retinal neurons. Cell transplantation is a promising option for AMD and clinical trials are underway using different cell types. Methods. We hypothesize that instead of focusing on a particular cell source for concurrent regeneration of all the retinal layers and also to prevent exhaustive research on an array of cell sources for regeneration of each layer, the choice should depend on, precisely, which layer is damaged. Results. Thus, for a damage limited to the retinal pigment epithelial (RPE) layer, the choice we suggest would be RPE cells. When the damage extends to rods and cones, the choice would be bone marrow stem cells and when retinal neurons are involved, relatively immature stem cell populations with an inherent capacity to yield neuronal lineage such as hematopoietic stem cells, embryonic stem cells, or induced pluripotent stem cells can be tried. Conclusion. This short review will prove to be a valuable guideline for those working on cell therapy for AMD to plan their future directions of research and therapy for this condition.